Incidence and Risk Factors for Heterotopic Ossification in a Matched Cohort Adolescent Population Undergoing Hip Arthroscopy. Issue 4 (7th April 2022) - Feroe, Aliya G.; Hassan, Mahad M.; Flaugh, Rachel A.; Maier, Stephen P.; Cook, Danielle L.; Yen, Yi-Meng; Kocher, Mininder S.
Abstract : Background: Heterotopic ossification (HO) is a known complication after hip arthroscopy in adults, positively associated with larger cam resection, male sex, older age, and obesity, and negatively associated with nonsteroidal anti-inflammatory drug (NSAID) use and capsular closure. However, it has not been well-documented in adolescents. The purpose of this study was to determine the incidence and risk factors for the development of HO in adolescent patients undergoing hip arthroscopy. Methods: Clinical and operative records from a pediatric institution were queried to identify patients aged 21 years or younger who underwent hip arthroscopy between 2008 and 2018. The 27 cases that developed HO were matched 1:4 on age and sex with 107 controls. The bivariate analysis assessed the relationship between demographic and perioperative factors on the development of HO. Multivariable logistic regression evaluated the association between prophylactic NSAID use (indomethacin 75 mg, 3 wk) and HO, controlling for surgeon and extent of cam resection (change in alpha angle). Results: Twenty-seven of 595 (4.5%) hips that underwent hip arthroscopy developed HO within 2 years of surgery. Prophylactic indomethacin was not significantly associated with developing HO [30% (8/27), P =0.83], after controlling for surgeon and extent of cam resection—nor were age, sex, and body mass index percentile. Of patients who developed HO, a smaller proportion underwent reoperation for HO excision among those who received prophylactic indomethacin than those who did not [13% (1/8) vs. 63% (12/19), P =0.03]. Conclusions: The incidence of HO within 2 years of hip arthroscopy in this adolescent population was 4.5%. Although studies in the adult hip arthroscopy population have pointed to a protective role of NSAIDs (eg, indomethacin) in radiographic HO, the effect was less certain in this adolescent sample. Larger studies are important to further evaluate the role of prophylactic NSAIDs and variations in arthroscopic technique in developing HO. Level of Evidence: Level III—therapeutic, case-control study.